2011
DOI: 10.1074/jbc.m111.259499
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-4-phosphate 5-Kinase and GEP100/Brag2 Protein Mediate Antiangiogenic Signaling by Semaphorin 3E-Plexin-D1 through Arf6 Protein

Abstract: The semaphorins are a family of secreted or membranebound proteins that are known to guide axons in the developing nervous system. Genetic evidence revealed that a class III semaphorin, semaphorin 3E (Sema3E), and its receptor Plexin-D1 also control the vascular patterning during development. At the molecular level, we have recently shown that Sema3E acts on Plexin-D1 expressed in endothelial cells, thus initiating a novel antiangiogenic signaling pathway that results in the retraction of filopodia in endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 46 publications
3
50
0
Order By: Relevance
“…Consistent with previous studies [20,45] HUVEC and human microvascular endothelial cells express Brag2a and Brag2b protein as assessed by Western blot (data not shown). Moreover, we confirmed that VEGF stimulation rapidly increases the activity of the small GTPase Arf6 in EC (supplemental Figures S1A and S1B) as previously reported [18,20,27].…”
Section: Role Of Brag2 In the Vegf-induced Activation Of Arf6supporting
confidence: 76%
See 4 more Smart Citations
“…Consistent with previous studies [20,45] HUVEC and human microvascular endothelial cells express Brag2a and Brag2b protein as assessed by Western blot (data not shown). Moreover, we confirmed that VEGF stimulation rapidly increases the activity of the small GTPase Arf6 in EC (supplemental Figures S1A and S1B) as previously reported [18,20,27].…”
Section: Role Of Brag2 In the Vegf-induced Activation Of Arf6supporting
confidence: 76%
“…Furthermore, the pharmacological inhibition of Arf6-GEFs of the cytohesin family with SecinH3 reduced angiogenesis [27]. Intriguingly, not only inhibition but also an over-activation of the Brag2/Arf6 pathway, as achieved by stimulation with Semaphorin 3E, blocks angiogenesis [44,45]. In conclusion, a stringent and balanced activation of Arf-GTPases by Brag2 is mandatory for efficient angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations